Analisis Kemampuan Penalaran Matematis Awal Siswa SMP dalam Memahami Permasalahan Koordinat Kartesius Berbasis RME - Ririn Nuraini; Andrea Arifsyah Nasution (Journal on Education, 2023)
This research was conducted with the aim of describing the initial mathematical reasoning ability level of junior high school students on the topic of Cartesian coordinates. This research uses descriptive qualitative method. The subjects in this study were 38 grade VIII students of SMP IT Al Hijrah Medan. The research instrument used was in the form of four questions worked on by students with a duration of 60 minutes. Data collection techniques in this study are through observation, interviews, and documentation. Documentation plays an important role in this research because it describes how the research process takes place. The research began with the observation stage, and continued with taking tests of students' mathematical reasoning abilities, then the researchers conducted interviews with students regarding student test results. The results showed that the students' initial mathematical reasoning abilities were still at a low level. In this case, the researcher found that students' initial reasoning abilities had not been able to help students in solving problems.